On Liberty in Talebof's Thought. Issue 3 (3rd May 2016) - Mazinani, Mehran
Abstract : This article represents Talebof 's thought on the modern idea of liberty defined in terms of selfishness, selflessness, and selfhood. First, a brief background is set forth in an attempt to show some of the influences on Talebof by others of the Iranian intelligentsia and European philosophers. Having set the stage, his philosophy is represented systematically, as against chronologically. This approach helps to reveal a shortcoming in Talebof 's philosophy regarding the modern idea of liberty. The shortcoming is evident: Talebof defined liberty in terms of selfishness and selflessness, but then did not dig deep enough to methodically examine selfhood as a more fundamental basis for liberty. The article argues that this shortcoming was caused by a number of factors, including philosophical poverty coupled with natural tendency for reification, and anxiously pragmatic ethos caused by lawlessness under the Qajars and exposure to the hegemonic West. In short, this paper defines the modern idea of liberty, describes Talebof 's understanding of it, and explains the obstacles that prevented Talebof from setting out a more comprehensive examination of the modern idea of liberty.